Necmettin Erbakan’ın Eğitim Anlayışı - Boyraz, Ekrem Zahid (2023)
Bu kitap, Necmettin Erbakan'ın eğitim anlayışını ele almaktadır. Yazar, Osmanlı'dan Cumhuriyet'e geçiş sürecinde kültür, medeniyet ve eğitim kavramlarını inceler. Kültür, medeniyet ve eğitim arasındaki ilişkiyi açıklar ve dönüşüm sürecini analiz eder. Ayrıca, Milli Görüş hareketinin kültür ve medeniyet perspektifindeki eğitim anlayışını ele alır. Bu kitap, Necmettin Erbakan'ın eğitim anlayışını anlamak ve değerlendirmek isteyen okuyucular için önemli bir kaynak niteliği taşımaktadır.This book examines Necmettin Erbakan's approach to education. The author explores the concepts of culture, civilization, and education during the transition from the Ottoman Empire to the Republic of Turkey. The book explains the relationship between culture, civilization, and education and analyzes the transformation process. Additionally, it discusses the educational perspective of the National Vision movement in terms of culture and civilization. This book serves as an important resource for readers who want to understand and evaluate Necmettin Erbakan's approach to education.